Реши уравнение:
(3x−4)2−(x−16)2=0.

ответ:
x1=
;x2=
(первым впиши меньший корень).

dididididdd dididididdd    3   17.04.2020 20:17    1

Ответы
taganrog123 taganrog123  17.04.2020 20:30

(3х - 4)² - (х-10)² =0

(3х - 4  - (х-10) )(3х-4 +х - 10)=0

(3х - 4  -х  +10)(4х -14) =0

(2х + 6)(4х-14) =0

2(х+3) * 2(2х-7) =0

4(х+3)(2х-7)=0

произведение = 0 , если один из множителей =0

х+3=0

х₁= -3     - меньший корень

2х-7 =0

2х = 7

х = 7 : 2  

х₂= 3,5

проверим:

(3* (-3)  - 4)²  -  (-3 - 10)²  = (-9-4)²   - (-13)² = (-13)²  - (-13)²= 169-169=0

(3 * 3,5  - 4)²  - (3,5 - 10)²  = (10,5 - 4)²  - (-6,5)² = 6,5²  - (-6,5)² =

= 42,25  - 42,25=0

ответ :  - 3.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра